Realismo como hipercorrelacionismo: Kant, Meillassoux, realismoespeculativo y filosofía trascendental - Romero Contreras, Arturo (2024)
The present paper offers a brief confrontation between Meillassoux’s speculative realism and Kant's transcendental idealism/empirical realism, as well as the critique the former addresses to the later. Meillassoux claims that Kant cannot think the object independently of the subject, what he calls «correlationism». Our hypothesis is that the radical separation demanded by Meillassoux renders knowledge of the real impossible. Methodologically, we offer a conceptual analysis in both authors as well as their corresponding implications for epistemology and ontology. We conclude that a subject-object separation fails to explain the link between things and thoughts. Kant, on the contrary, delivers the grounds to explain the contact between things, intuitions, and concepts. This entails a more subtle analysis of the world and subjectivity offering different intersecting levels. These different levels are linked differently, offering the picture of a hyperconnected world, instead of a simple subject-object divide.